2022
DOI: 10.3390/ijms23020700
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Polyunsaturated Fatty Acid Intake and Risk of Neurodevelopmental Impairment in Premature Infants

Abstract: The N3 and N6 long chain polyunsaturated fatty acids (LCPUFA) docosahexaenoic acid (DHA) and arachidonic acid (AA) are essential for proper neurodevelopment in early life. These fatty acids are passed from mother to infant via the placenta, accreting into fetal tissues such as brain and adipose tissue. Placental transfer of LCPUFA is highest in the final trimester, but this transfer is abruptly severed with premature birth. As such, efforts have been made to supplement the post-natal feed of premature infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 102 publications
0
14
0
Order By: Relevance
“…Additionally, it has been demonstrated that human milk ARA levels are higher with increased ARA supplementation ( 41 ). Although several studies in very preterm infants have shown a decrease in LCPUFA levels compared to term infants ( 3 , 42 ) and existing evidence supports LCPUFAs supplementation in these infants ( 43 ), doses, the route of administration, and the choice of better LCPUFA supplementation remain unknown. According to our data, 120:60 ARA:DHA supplementation increased DHA metabolite levels compared to lower doses (80:40 ARA:DHA), without a significant increase in DHA plasma levels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that human milk ARA levels are higher with increased ARA supplementation ( 41 ). Although several studies in very preterm infants have shown a decrease in LCPUFA levels compared to term infants ( 3 , 42 ) and existing evidence supports LCPUFAs supplementation in these infants ( 43 ), doses, the route of administration, and the choice of better LCPUFA supplementation remain unknown. According to our data, 120:60 ARA:DHA supplementation increased DHA metabolite levels compared to lower doses (80:40 ARA:DHA), without a significant increase in DHA plasma levels.…”
Section: Discussionmentioning
confidence: 99%
“…109 In the first week after birth, the levels of DHA and AA might drop due to the lack of adipose reserves and insufficient FA intake by the mother. 110 The LC-PUFA content in HM in the United States, Europe, and Africa is similar, except for higher amounts of ω-3 LC-PUFAs in the milk of women whose diets contain a large quantity of fish. 111,112 Arachidonic acid (C20:4 ω-6) is an important LC-PUFA in HM.…”
Section: Mono-and Polyunsaturated Fatty Acids In Hmmentioning
confidence: 99%
“…Consequently, preterm neonates should be maintained within this range during the postnatal period. Moreover, substantial reductions in mean DHA levels in preterm neonates were seen during the first postnatal week and remained for three weeks, and decreased postnatal DHA levels in premature infants were associated with an in-creased risk of BPD [59]. A post-hoc study of the Trial to Improve Neurodevelopmental Outcomes (2001 to 2005) found that giving DHA supplements to pregnant mothers reduced supplementary oxygen requirements in newborns weighing less than 1250 g at birth 36 weeks after menopause [60].…”
Section: Docosahexaenoic Acidmentioning
confidence: 99%